Structural elucidation, and morphological and magnetic behavior evaluations, of low-temperature sintered, Ce-doped, nanostructured garnet ferrites. (May 2018) - Akhtar, Majid Niaz; Ali, Kashif; Umer, Asim; Ahmad, Tahir; Khan, Muhammad Azhar
Graphical abstract: Highlights: Cex Gd3.5-x Fe4.5 O12 were synthesized via sol gel self-combustion route. Crystallite size was found in the range of 20–38 nm. Morphology of Ce-Gd doped and undoped garnets were observed systematically. Switching field distribution was calculated for further applications of the nanoferrites. These garnets also have potential applications in microwave high frequency devices. Abstract: Low-temperature sintered Cex Gd3.5-x Fe4.5 O12 (x = 0.0, 0.4, 0.8, 1.2, 1.6, 2.0 and 2.4) garnet ferrites were synthesized via a sol-gel self-combustion route. Phase, structure, morphology and magnetic investigations were done using FTIR, XRD, FESEM, and VSM, respectively. Single-phase structures of all Ce 3+ substituted nano-sized garnet ferrites were confirmed through XRD. The crystallite size was decreased with Ce 3+ incorporation. Relevant structural parameters such as site radii, bond lengths, ionic radii, and shared edges were calculated using XRD. The vibrational spectroscopy stretching band studies were also done using FTIR. The grain size and morphology were also analyzed using FESEM. The magnetic remanance, saturation, and coercivity were found to increase systematically with an increase in Ce 3+ concentration in these garnets. Switching field distribution curves were also plotted using the first derivative of the demagnetization data from MH loops. The better magnetic properties of these nanogarnets suggest their use for miniaturization of the devices in various applications.